2009
DOI: 10.1089/aid.2009.0027
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of HIV Type 1 in Northern Brazil: Identification of Subtypes C and D and the Introduction of CRF02_AG in the Amazon Region of Brazil

Abstract: The molecular epidemiology of HIV-1 strains circulating in Belem-PA and Macapa-AP, in the Northern region of Brazil, is described using sequences of the C2V3 segment of the env and the pro gene of HIV-1 from patients of the Reference Unit for Special Infectious and Parasitary Diseases (URE-DIPE) in Belem-PA and the Central Laboratory (LACEN) in Macapa-AP. Subtype B was the most frequently found in relation to pro (88.3%) in Belem and in Macapa (97.1%) and env (88.3% in Belem and 100% in Macapa). Subtype F was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
37
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 43 publications
8
37
1
1
Order By: Relevance
“…1). [2][3][4][5] However in the Southern region, a distinct profile is observed. Currently, depending on the state, 27-79% of HIV infections are caused by HIV-1C, 23-45% by HIV-1B, 3-29% by CRF31 BC and other BC recombinants, and HIV-1F and its recombinants account for up to 10% of infections.…”
Section: Introductionmentioning
confidence: 99%
“…1). [2][3][4][5] However in the Southern region, a distinct profile is observed. Currently, depending on the state, 27-79% of HIV infections are caused by HIV-1C, 23-45% by HIV-1B, 3-29% by CRF31 BC and other BC recombinants, and HIV-1F and its recombinants account for up to 10% of infections.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 In Brazil, the major circulating HIV-1 subtype is B (HIV-1B), yet other subtypes such as A1, C, D, F1, BF1, and BC recombinants have also been found. [4][5][6][7] The southern region of Brazil is unique, with an endemicity of HIV-1 subtype C (HIV-1C). Several studies have reported an increase in HIV-1C prevalence in that region.…”
Section: Introductionmentioning
confidence: 99%
“…The subtypes C, F1 and the recombinants BC and BF are usually observed at low frequencies in the majority of Brazilian cities and states (4) (5) (6) (7) (8) (9) (10) . The South Region (States of Rio Grande do Sul, Santa Catarina, and Paraná) contains 20% of Brazilian HIV-1/AIDS patients, with high rates of incidence (31.1 patients/100,000 inhabitants) and mortality (8.1 deaths/100,000 inhabitants) (3) .…”
mentioning
confidence: 99%